Discussion Of Power Through The Eyes Of The Margins: Praxis Of Post-colonial Aeta Indigenous Women Healers In The Philippines - Torres, Rose; Nyaga, Dionisio (Penerbit Universiti Sains Malaysia (USM Press), 2016)
This article is based on a research study conducted in the Philippines. It explores the experiences of Aeta Indigenous women healers on how power becomes deconstructed through their stories and practices. This study employs the Talking Circle as a methodology to legitimate the voices and experiences of Aeta Indigenous women healers, and draws on this knowledge to remedy the systemic exclusion of Indigenous knowledge in the academy. These stories unveil the contribution of Aeta Indigenous women healers to the discourse of power.